2012
DOI: 10.1016/j.bbadis.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Familial hemiplegic migraine type 1 mutations W1684R and V1696I alter G protein-mediated regulation of CaV2.1 voltage-gated calcium channels

Abstract: Familial hemiplegic migraine type 1 (FHM-1) is a monogenic form of migraine with aura that is characterized by recurrent attacks of a typical migraine headache with transient hemiparesis during the aura phase. In a subset of patients, additional symptoms such as epilepsy and cerebellar ataxia are part of the clinical phenotype. FHM-1 is caused by missense mutations in the CACNA1A gene that encodes the pore-forming subunit of Ca(V)2.1 voltage-gated Ca(2+) channels. Although the functional effects of an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…In this altered conformation, SNARE binding to the synprint site may no longer exert the same forces that are required for inactivation of the channel. Similar studies have also shown that migraine mutations in Ca V 2.1 affect the influence of regulatory proteins including SNAREs (21), G proteins (38,39), and calmodulin-mediated facilitation (27).…”
Section: Volume 288 • Number 47 • November 22 2013mentioning
confidence: 86%
“…In this altered conformation, SNARE binding to the synprint site may no longer exert the same forces that are required for inactivation of the channel. Similar studies have also shown that migraine mutations in Ca V 2.1 affect the influence of regulatory proteins including SNAREs (21), G proteins (38,39), and calmodulin-mediated facilitation (27).…”
Section: Volume 288 • Number 47 • November 22 2013mentioning
confidence: 86%
“…Studies of recombinant human Ca v 2.1 channels carrying five different FHM1 mutations have shown that the migraine mutations reduce G-protein-mediated inhibitory modulation of Ca v 2.1 channels (Melliti et al 2003;Weiss et al 2008;Serra et al 2009;Garza-Lopez et al 2012), an effect that may lead to further gainof-function of Ca influx through mutant channels during neuromodulation. The only study that investigated voltage-dependent G-protein modulation using physiological-like stimuli revealed a reduced Gbc-mediated inhibition of the Ca current evoked by AP-like stimuli and a reduced facilitation of the Ca current carried by mutant channels after a train of short depolarizing pulses in cells overexpressing Gbc subunits; the reduction of G-protein modulation was dependent on the duration of the AP, being larger with APs of longer duration (Serra et al 2009).…”
Section: Effect Of Fhm1 Mutations On Modulation Of Ca V 21 Channelsmentioning
confidence: 99%
“…1.1) shifts to lower voltages of activation of recombinant mutant channels were also revealed by measurements of whole-cell current in heterologous expression systems (Kraus et al 1998(Kraus et al , 2000Hans et al 1999;Tottene et al 2002Tottene et al , 2005Melliti et al 2003;Mullner et al 2004;Weiss et al 2008;Adams et al 2009;Serra et al 2009;Garza-Lopez et al 2012) and transfected neurons (where five FHM1 mutations, underlined in Fig. 1.1, were analyzed) (Tottene et al 2002(Tottene et al , 2005.…”
Section: Effect Of Fhm1 Mutations On the Biophysicalmentioning
confidence: 99%
“…Despite the large number of mutations characterized at each FHM locus, only a small fraction of mutations that produce very extreme phenotypes have been studied in genetically altered mice given the expense and time involved in generating modified animals [58]. …”
Section: Molecular Genetic Studies Of Migrainementioning
confidence: 99%